(untitled) (Contemporary Mathematics, 2025)
The Stochastic Graphene Sheets Equation (SGSE) is taken into consideration in this study. By applying two different methods such as the Sardar subequation method and Jacobi Elliptic Function (JEF) method, we obtain new periodic solitons, dark and bright solitons, anti-Kink and Kink solitons solutions for the SGSE. Because graphene sheets are important in many fields, such as electronics, photonics, and energy storage, the solutions of the stochastic graphene sheets model are beneficial in understanding several fascinating scientific phenomena. Using MATLAB, we exhibit several 2D and 3D graphs that illustrate the impact of multiplicative noise on the exact solutions of SGSE.